Les photographies du paysage : quelles analyses des dynamiques paysagères ? - Caroline Guittet; Laurence Le Dû-Blayo (Projets de Paysage)
Diachronous photographic series are didactic resources for understanding landscape dynamics. In fact, several experiments, using quantitative and qualitative methods, attest to this interest in analysing photographs. The example of documents on urban dynamics in Brittany (France) makes it possible to study potentials of both corpus and methods. The utilization of photographic observatories of landscape (Observatoires photographiques du paysage, OPP) and of an iconographic complementary fund with a qualitative approach gives a detailed reflection of landscape dynamics. In other words, this corpus is representative of the regional dynamics from the century scale to the multiannual scale through identification of local specificities and practices in connection with the landscape.